Corporate Social Responsibility (CSR) dan Profitabilitas Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2018-2021 - Velli Maita Putri; Endrawati Endrawati; Elfitri Santi (Politeknik Negeri Padang, 2023)
This study was conducted to describe the variables Corporate Social Responsibility (CSR) and profitability. This study uses a quantitative approach method. The data analysis technique used in this research is descriptive statistics. Disclosure of the economic, environmental, and social aspects of CSR as independent variables, and projected profitability with Return on Assets (ROA) and Net Profit Margin (NPM) as dependent variables. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021. The sample selection in this study used purposive sampling method and obtained 29 sample companies. The results of this study indicate that the largest value of company size is found in the automotive and component sub-sector where the disclosure of CSR indicator item is also above the average and the ROA and NPM values are also high with NPM value is the highest among other sub-sectors. While the smallest value of the average company size is found in the chemical sub-sector where the disclosure of CSR indicator item is also below the average and the ROA and NPM values are also below average.